Representation of solutions of systems of linear differential equations with multiple delays and linear parts given by nonpermutable matrices - Medveď, M.; Pospíšil, M. (Нелінійні коливання, 2016)
In recent results on representation of solutions of systems of delayed differential equations the condition that the linear parts are given by pairwise permutable matrices was assumed. In this paper it is shown how this strong condition can be avoided, and representation of solutions of systems of differential equations with nonconstant coefficients and variable delays is derived. The results are applied to a system with two constant delays. Also the nonexistence of blow-up solutions is proved for nonlinear systems.